Advances of Microfluidics in Biomedical Engineering. Issue 6 (13th February 2019) - Zhong, Qifeng; Ding, Haibo; Gao, Bingbing; He, Zhenzhu; Gu, Zhongze
Abstract: As an enabling technique, microfluidic systems have developed rapidly in recent years to emerge as a powerful tool in the field of biomedical engineering. Microfluidics enables miniaturized, integratable, high‐throughput and automated biochemical analysis, fabrication of biomaterials with precisely controlled structures and compositions, and construction of organ‐on‐a‐chip systems with specific organ features and functions. Recent advances in microfluidics for biomedical engineering applications are outlined in this review, emphasizing the basic concepts and research trends in this field. The review covers recent research in microfluidics for bioassays, biofabrication, and tissue engineering. The technologies involved in these applications are highlighted, such as those for fabricating sensitive and portable bioassays, for fabricating biomaterials in a regulated manner, and for fabricating 3D cell culture scaffolds and microenvironments. Abstract : The recent advances in microfluidics for biomedical engineering applications are summarized. Emphasis is given to the basic concepts and research trends in this field. The review covers recent research in microfluidics for bioassays, biofabrication, and tissue engineering. The device design and technologies involved in these applications are highlighted.